Supportive care needs and psychosocial outcomes of rural versus urban women with breast cancer. Issue 11 (16th July 2022) - Eggins, Renee; Fowler, Helen; Cameron, Jessica; Aitken, Joanne F.; Youl, Philippa; Turrell, Gavin; Chambers, Suzanne K.; Dunn, Jeff; Pyke, Chris; Baade, Peter D.; Goodwin, Belinda
Abstract: Objective: To identify whether supportive care needs vary according to remoteness and area–level socio‐economic status and to identify the combinations of socio‐demographic, area‐level and health factors that are associated with poorer quality of life, psychological distress and severity of unmet supportive care needs. Methods: Cross sectional data was collected from women with a breast cancer diagnosis ( n = 2635) in Queensland, Australia, through a telephone survey including socio‐demographic, health, psychosocial and supportive care needs measures. Hierarchical regression and cluster analyses were applied to assess the predictors of unmet need and psychosocial outcomes and to identify socio‐demographic and health status profiles of women, comparing their level of unmet needs and psychosocial outcomes. Results: Women living in outer regional areas reported the highest severity of unmet need in the patient care domain. Greater unmet need for health systems and information and patient care was also evident for those in moderately and most disadvantaged areas. Three clusters were identified reflecting (1) older women with poorer health and lower education (19%); (2) younger educated women with better health and private insurance (61%); and (3) physically active women with localised cancer who had completed treatment (20%). Poorer outcomes were evident in the first two of these clusters. Conclusions: This better understanding of the combinations of characteristics associated with poorer psychosocial outcomes and higher unmet need can be used to identify women with higher supportive care needs early and to target interventions.